Hermeneutical Perspectives on the Theology of Daily Life in Comic Book Stories - Reblin, Iuri Andréas (Estudos teológicos, 2014)
This study presents hermeneutical perspectives on the theology of daily life in comic book stories through a descriptive approach, stemming from a doctoral research grounded in a bibliographical and exploratory reading with a case study analysis. The study assumes the theology of daily life, that is, the use, in the sense understood by Michel de Certeau, which the authors of the comic make from religious elements, stitching them into their history and the centrality of narrative in the process of constitution of the human world. From this premise, it presents a possible reading of the theology of daily life in comic books from the super adventure genre. The research closes indicating thematic, methodological and ideological approaches between theology and super adventure. Theology and super adventure deal with the values dear to the human being, with the mythic structure and the human faculty of conceiving the ideal and adding it to the real.